Nutritional Composition and Digestibility of Water Hyacinth and Water Pennywort - Pattanee Jantrarotai, (Agriculture and Natural Resources, 1993)
Water hyacinth (Eichhornia crassipes) and water pennywort (Hydrocotyle ranunculoides) collected from waste treating ponds receiving wastewater from chicken houses were evaluated for the feasibility of using as livestock feeds. The averaging nutritive contents for crude protein, crude fat, acid detergent fiber and ash were 18%, 1%, 33% and 17% for water hyacinth and 24%, 2%, 29% and 18% for water pennywort, respectively. The amino acids contents of these aquatic plants were reported. In vitro dry matter digestibility for water hyacinth and water pennywort by using enterogastric juice of a cattle as digestive fluid were 48% and 69%, respectively. Except for high moisture contents, the nutritive values and dry matter digestibility of water hyacinth and water pennywort were comparable to alfalfa for using as feed for livestocks.